USE OF PEDAGOGICAL, INFORMATION AND COMMUNICATION TECHNOLOGIES IN EFFECTIVE ORGANIZATION OF THE EDUCATIONAL PROCESS - Pardayev, Sherzod (Журнал иностранных языков и лингвистики, 2023)
Five initiatives put forward by our President three years ago have become an integral part of our spiritual life today. This article contains information about the importance of changing today's educational system, raising it to the level of modern requirements, in a word, the importance of the teacher being active with the times.